La succession « ab intestat » et testamentaire - Portugais, Marcel (Assurances)

(untitled) (HEC Montréal, 1984)
Me. Marcel Portugais looks at various aspects of wills in Quebec. His article presents possible solutions, with their advantages, their drawbacks and points to be checked.